Accounting Ethical Practices and Financial Reporting Quality: A Case of Mukwano Group of Companies - Esther Kerlen Nabwire (Uganda Christian University, 2024)
This research was aimed at the Accounting Ethical practices and financial reporting Quality by Mukwano group of companies. This study based on three main objectives which were: To examine the effects of disclosure on the Quality of financial reports of Mukwano group of companies, to examine the effects of objectivity on the quality of financial reports of Mukwano group of companies, to examine the effects of integrity on the quality of financial reports of Mukwano group of companies. The researcher used both qualitative and quantitative research designed with a sample of 40 respondents. Qualitative data was obtained through uestionnaires and interviews while Quantitative data was obtained through computation and analysis. The collected data was analyzed using Microsoft Excel and presentation in the form of tables. The findings of this study reveal that a strong commitment to ethical principles in accounting significantly contributes to the quality of financial reporting. The research identifies key ethical challenges faced by the organization and offers recommendations on how Mukwano Group of Companies can further strengthen its ethical framework to ensure the highest standards of financial reporting. This study not only contributes to the academic discourse on accounting ethics and financial reporting but also provides practical insights for companies striving to improve their financial reporting processes through ethical conduct.